Impact evaluation of the teaching and research process of the General Teaching Hospital of Calderón Quito-Ecuador - Olmedo-Pérez, Luis Fernando (2024)
The Impact Evaluation Study of the teaching and research process of the Calderón General Teaching Hospital-HGDC in the city of Quito-Ecuador in the period 2016-2022, aims to measure the impact of the Teaching and Research process with respect to: (1) academic process and resources, (2) evaluation and research, (3) learning, training and knowledge transfer and (4) clinical-surgical practice and performance; through the design and application of the impact evaluation methodology with a focus on measurable results, Balanced Scorecard-BSC. The target group was identified as undergraduate students, rotating interns, postgraduate students, teachers and health care personnel of the Higher Education Institutions (HEI) that perform their health care and academic activities at the HGDC. It was developed in three phases: the first comprises the period 2016-2020, with a total population of 949 participants and an effective sample of 291 participants, served as a baseline for the construction of the follow-up and monitoring matrix-BSC. The second phase of 2021 has 382 participants and an effective sample of 165. The third phase of 2022 has a total population of 344 and an effective sample of 128 participants. The BSC monitoring matrix resulted that the average Global Effective Impact Evaluation of the HGDC Teaching and Research process in the period 2016-2022 reached 87.39% effectiveness, reflecting that the care and teaching activities are adequately fulfilled. The research provides conclusions and suggestions aimed at improving the care and teaching processes of the hospital and allows it to be a model replicated for other institutions.